Elaborasi Hukum Membayar Zakat Fitrah Menggunakan Dompet Digital dalam Perspektif Islam - Afif Surya Fakhrian; Ari Prasteyo; Pinki Cahyaningrum (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
Islam teaches that in property in which there are rights of others. Therefore, Islam requires the existence of zakat, qurban, waqf, almsgiving, infaq, aqiqah, zakat, respecting guests and neighbors, as well as issuing hartanta to realize public welfare and various other worship in social terms. Zakat can be termed as the right of Allah that exists in man that must be conveyed to others who are entitled, in which all Muslims who have achieved nisab and haul are obliged to carry out zakat. Along with the times, muamalah activities in this life can be carried out digitally. Especially in terms of worship such as zakat fitrah. There are several digital platforms that provide various services, one of which is online or digital zakat payment services. This raises questions among the public, regarding the definition, legal basis, mandatory requirements and legal requirements, and wisdom of zakat fitrah? How is the application of zakat fitrah with digital money or online? And how is the law of zakat fitrah with digital money? In the Islamic view, zakat which is done online is allowed, but this still does not leave the terms or conditions in zakat. Muzakki from the outset of the berzakat had expressed the intention to make a difference. The zakat funds will still reach the hands of amil zakat to be handed over to people who are entitled to receive them. Zakat Fitrah would be better done directly with staple food, but if in urgent circumstances it can be carried out online or using digital money.